2021
DOI: 10.2478/ttj-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Prediction of Vehicles Speed in Free-Flow Traffic

Abstract: Speed is a crucial factor in the frequency and severity of road accidents. Light and heavy vehicles speed in free-flow traffic at six locations on Poland’s national road network was analyzed. The results were used to formulate two models predicting the mean speed in free-flow traffic for both light and heavy vehicles. The first one is a multiple linear regression model, the second is based on an artificial neural network with a radial type of neuron function. A set of the following input parameters is used: av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Compared with linear interpolation, this can better reflect the change trend of the signal. Maczy ński et al [59] developed an artificial neural network with radial neural functions driven by group parameters (i.e., average hourly traffic, the percentage of vehicles in free-flow traffic, geometric parameters of the road section (lane and hard shoulder width), and type of day and time) for predicting vehicle speeds. To reduce the errors of existing methods in short-term speed prediction and be able to predict medium-to long-term traffic speeds, Zhang et al [60] proposed a traffic speed prediction method named ASTCN that combines attention and spatio-temporal features.…”
Section: Modern Deep Learning Methodsmentioning
confidence: 99%
“…Compared with linear interpolation, this can better reflect the change trend of the signal. Maczy ński et al [59] developed an artificial neural network with radial neural functions driven by group parameters (i.e., average hourly traffic, the percentage of vehicles in free-flow traffic, geometric parameters of the road section (lane and hard shoulder width), and type of day and time) for predicting vehicle speeds. To reduce the errors of existing methods in short-term speed prediction and be able to predict medium-to long-term traffic speeds, Zhang et al [60] proposed a traffic speed prediction method named ASTCN that combines attention and spatio-temporal features.…”
Section: Modern Deep Learning Methodsmentioning
confidence: 99%
“…In the first stage, as presented in Figure 3, SSMs should be applied. In Maczyński et al (2021) a correlation between overall traffic volumes and the percentage of vehicles exceeding the speed limit, either for light and heavy vehicles was shown. Among the 13 traffic parameters initially considered (Table 4), both hourly volumes of heavy and light vehicles, as well as hourly statistics on speeds and their distributions for both groups of vehicles were therefore included.…”
Section: Model For Identifying Road Risk Classmentioning
confidence: 97%
“…Based on a survey conducted in Poland, it was found that for a speed limit of 90 km/h in free traffic conditions, 38% of light vehicles exceed the speed limit during the day and 42% at night. For heavy vehicles with a limit of 70 km/h, speed limit exceeding of this class of vehicles in same traffic flow conditions is 83.5% in the day and 86% at night [29]. Research focused on the credibility of the 80 km/h speed limit of two-lane rural roads, where drivers verified the proposed speed for each of 27 road situations, which shows that there were large differences in drivers' attitudes for different road and environmental characteristics related to (non) compliance with the limits in given situations [16].…”
Section: Literature Reviewmentioning
confidence: 97%